Validation of the Chinese Version of the Self-Objectification Beliefs and Behaviors Scale - Lang, Min; Ye, Yiduo (Frontiers in Psychology, 2021)
Given the limitations of the existing tools used for measuring self-objectification in China, this study aimed to validate the Chinese version of the Self-Objectification Beliefs and Behaviors Scale (C-SOBBS). In this study, we translated and culturally adapted the SOBBS to the Chinese context. Data from a sample of female college students (n = 331) were used to test the validity of the C-SOBBS. The confirmatory factor analysis validated the factor structure of the C-SOBBS and the relationship between the C-SOBBS and its factors and four other measures demonstrated that the C-SOBBS has a strong construct and convergent validity. Furthermore, the results of hierarchical multiple regression demonstrated the C-SOBBS’s incremental validity related to the Female Questionnaire of Trait Self-Objectification and Objectified Body Consciousness-Surveillance subscale. Additionally, data from 76 young Chinese women showed that the C-SOBBS had good test-retest stability over a two-week period. The results of this study demonstrate the utility of the C-SOBBS to assess the self-objectification beliefs and behaviors of young Chinese women within the context of Chinese culture.